Intergenerational association of adverse childhood experiences and perinatal mental health in adult female offspring: evidence from the longitudinal grandmothers, mothers, and their Children's health study in ChinaResearch in context - Hui Wang; Yue Zhang; Weijie Ding; Jiyue Dai; Xiaoqin Zhu; Xiaolin Xu (The Lancet Regional Health. Western Pacific)
Summary: Background: The cycle of maltreatment theory posits a linkage between mothers' and offspring's exposures to adverse childhood experiences (ACEs), and their associations with offspring's early-life mental health; however, such associations in adulthood remain unclear. This study aims to examine the intergenerational association between mothers' ACEs, offspring's ACEs, and offspring's mental health from pregnancy to three years after childbirth, and to explore the potential pathways. Methods: We used data on 1931 mother-offspring dyads from the longitudinal Grandmothers, Mothers, and Their Children's Health study in Huai'an city, China. ACEs were retrospectively assessed based on the Childhood Trauma Screener. Offspring's symptoms of anxiety and depression were measured through self-reported diagnoses or symptoms and standard questionnaires (the 7-item Generalized Anxiety Disorder Scale for anxiety and the 10-item Centre for Epidemiological Studies Depression Scale for depression) during pregnancy, one year and three years after childbirth. Logistic regression models were conducted to estimate the associations. The structural equation model (SEM) was used to examine the potential mediating pathways. Findings: A total of 367 (19.0%) mothers and 271 (14.0%) female offspring reported the history of ACEs. Female offspring of mothers with ACEs also had higher odds of exposure to ACEs (odds ratio [OR] = 3.37, 95% confidence interval [CI]: 2.51–4.53). Mothers' and female offspring's exposures to ACEs were both associated with higher odds of offspring experiencing mental disorders during the perinatal period. For example, female offspring with ACEs had 2.05-fold (95% CI: 1.54–2.72), 2.41-fold (95% CI: 1.75–3.33), and 2.30-fold (95% CI: 1.58–3.33) increased odds of the anxious or depressive symptoms during pregnancy, one year, and three years after childbirth, respectively, compared to offspring without ACEs. Results from the SEM indicated that mothers' ACEs and female offspring's perinatal mental health were linked mainly through the mediation role of female offspring's ACEs. Interpretation: Mothers' and female offspring's likelihood of exposure to ACEs are intergenerationally associated and are both related to offspring's perinatal mental health. Female offspring's ACEs mediate the association between mothers' ACEs and female offspring's adulthood mental health. Our findings highlight the need for policies to break the cycle of maltreatment and promote women's mental health across multiple generations, in particular through family-based interventions. Funding: This study was supported by the National Natural Science Foundation of China (72474197), China Medical Board Open Competition Program (21-416), Key Medical Program of Jiangsu Health Commission (ZD2021044), and Huai'an Science and Technology Program (HAB2024039).